Environmental Contamination with Candida Species in Multiple Hospitals Including a Tertiary Care Hospital with a Candida auris Outbreak - Jessica Ann Kumar; Brandon Eilertson; Jennifer L. Cadnum; Chauna S. Whitlow; Annette L. Jencson; Nasia Safdar; Sarah L. Krein; Windy D. Tanner; JeanMarie Mayer; Matthew H. Samore; Curtis J. Donskey (Pathogens and Immunity, 2019)
Background: Environmental sources have been implicated as a potential source for exogenous acquisition of Candida species, particularly the emerging multidrug-resistant Candida auris. However, limited information is available on environmental reservoirs of Candida species in healthcare facilities.